Is a Nomogram Able to Predict Postoperative Wound Complications in Localized Soft-tissue Sarcomas of the Extremity?. Issue 3 (March 2020) - Bedi, Meena; Ethun, Cecilia G.; Charlson, John; Tran, Thuy B.; Poultsides, George; Grignol, Valerie; Howard, J. Harrison; Tseng, Jennifer; Roggin, Kevin K.; Chouliaras, Konstantinos; Votanopoulos, Konstantinos; Cullinan, Darren; et al.
Abstract: Background: Postoperative wound complications are challenging in patients with localized extremity soft-tissue sarcomas. Various factors have been associated with wound complications, but there is no individualized predictive model to allow providers to counsel their patients and thus offer methods to mitigate the risk of complications and implement appropriate measures. Questions/purposes: We used data from multiple centers to ask: (1) What risk factors are associated with postoperative wound complications in patients with localized soft-tissue sarcomas of the extremity? (2) Can we create a predictive nomogram that will assess the risk of wound complications in individual patients after resection for soft-tissue sarcoma? Methods: From 2000 to 2016, 1669 patients undergoing limb-salvage resection for a localized primary or recurrent extremity soft-tissue sarcoma with at least 120 days of follow-up at eight participating United States Sarcoma Collaborative institutions were identified. Wound complications included superficial wounds with or without drainage, deep wounds with drainage because of dehiscence, and intentional opening of the wound within 120 days postoperatively. Sixteen variables were selected a priori by clinicians and statisticians as potential risk factors for wound complications. A univariate analysis was performed using Fisher's exact tests for categorical predictors, and Wilcoxon's rank-sum tests were used for continuous predictors. A multiple logistic regression analysis was used to train the prediction model that was used to create the nomogram. The prediction performance of the datasets was evaluated using a receiver operating curve, area under the curve, and calibration plot. Results: After controlling for potential confounding factors such as comorbidities, functional status, albumin level, and chemotherapy use, we found that increasing age (odds ratio 1.02; 95% confidence interval, 1.00-1.03; p = 0.008), BMI (OR 1.05; 95% CI, 1.02-1.09; p = 0.004), lower-extremity location (OR 6; 95% CI, 2.87-12.69; p < 0.001), and neoadjuvant radiation (OR 2; 95% CI, 1.47-3.16; p < 0.001) were associated with postoperative wound complications (area under the curve 69.2% [range 62.8%-75.6%]). Conclusions: We found that age, BMI, tumor location, and timing of radiation are associated with the risk of wound complications. Based on these factors, a validated nomogram has been established that can provide an individualized prediction of wound complications in patients with a resected soft-tissue sarcoma of the extremity. This may allow for proactive management with nutrition and surgical techniques, and help determine the delivery of radiation in patients with a high risk of having these complications. Level of Evidence: Level III, therapeutic study.